2021
DOI: 10.1177/26334895211037391
|View full text |Cite
|
Sign up to set email alerts
|

The psychometric and pragmatic evidence rating scale (PAPERS) for measure development and evaluation

Abstract: To rigorously measure the implementation of evidence-based interventions, implementation science requires measures that have evidence of reliability and validity across different contexts and populations. Measures that can detect change over time and impact on outcomes of interest are most useful to implementers. Moreover, measures that fit the practical needs of implementers could be used to guide implementation outside of the research context. To address this need, our team developed a rating scale for imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(73 citation statements)
references
References 15 publications
0
73
0
Order By: Relevance
“…managing or acquiring resources). In 4 of the 6 studies (66.7%) [ 59 , 61 , 68 , 79 ], the used champion subscale had acceptable internal consistency ( α ≥ 0.70 [ 97 ]); one study (16.7%) reported that the used champion subscale had low internal consistency ( α = 0.43) [ 50 ]. In 2 of the 6 studies (33.3%), the authors conducted an exploratory factor analysis and reported that the champion items loaded highly to a single factor [ 68 , 77 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…managing or acquiring resources). In 4 of the 6 studies (66.7%) [ 59 , 61 , 68 , 79 ], the used champion subscale had acceptable internal consistency ( α ≥ 0.70 [ 97 ]); one study (16.7%) reported that the used champion subscale had low internal consistency ( α = 0.43) [ 50 ]. In 2 of the 6 studies (33.3%), the authors conducted an exploratory factor analysis and reported that the champion items loaded highly to a single factor [ 68 , 77 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…The pragmatic and psychometric evidence of each eligible measure was assessed and scored using the Psychometric and Pragmatic Evidence Rating Scale (PAPERS) [ 17 , 31 ]. PAPERS includes 14 items that assesses nine psychometric properties and five pragmatic features (see Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Measures should also illustrate reliability and evidence of other domains of validity (e.g., concurrent validity), to ensure accuracy and reduce error. Finally, measures should exhibit important pragmatic qualities, including easy access, use, scoring, and interpretation [ 17 ]. Pragmatic qualities are less frequently evaluated but are essential in ensuring the uptake of reliable and valid measures.…”
Section: Introductionmentioning
confidence: 99%
“…This study's strengths include the use of established measure development best practices ( 27 , 28 , 39 ), engagement of key partners, including target end users, in each development stage, and transparent reporting of early findings so that they may be used by other researchers and practitioners ( 56 ). This study contributes to filling a gap in the measure development methods literature in that we provide detail on processes for identifying relevant constructs and engaging target audiences in developing and refining measures often not detailed in the literature.…”
Section: Discussionmentioning
confidence: 99%